Marasmius margallensis, a new species of Marasmius sect. Sicci from Margalla Hills, Pakistan - Razzaq, Fauzia; Khalid, Abdul Nasir (Phytotaxa, 2023)
Marasmius margallensis sp. nov. of sect. Sicci from Margalla hills, Islamabad, Pakistan, is described and illustrated, based on morphological characteristics and multigene phylogenetic analyses. The taxon is characterized by a pale yellow to dull orange pileus with light gray margins, clavate to narrowly fusiform basidiospores, rather short pleurocystidia and hymeniderm pileipellis with Siccus-type broom-cells. Marasmius pulcherripes is closest relative of the newly described species M. margallensis in sect. Sicci in phylogenetic analyses but the later one is distinct by macro-, and micro-morphological features and molecular data.